Annular closure device lowers reoperation risk 4 years after lumbar discectomy - Nanda, Dharmin; Arts, Mark P; Miller, Larry E; Köhler, Hans-Peter; Perrin, Jason M; Flüh, Charlotte; Vajkoczy, Peter (Medical devices (Auckland, N.Z.), 2019)
To determine whether implanting an annular closure device (ACD) following a lumbar discectomy procedure in patients with large defects in the annulus fibrosus lowers the risk of reoperation after 4 years. In a multicenter randomized trial, patients with large annular defects following single-level lumbar discectomy were intraoperatively randomized to additionally receive an ACD or no treatment (Controls). Clinical and imaging follow-up were performed at routine intervals over 4 years of follow-up. Main outcomes included reoperations at the treated lumbar level, leg pain scores on a visual analog scale, Oswestry Disability Index (ODI), and Physical Component Summary (PCS) and Mental Component Summary (MCS) scores from the SF-36 questionnaire. Among 550 patients (ACD 272, Control 278), the risk of reoperation over 4 years was 14.4% with ACD and 21.1% with Controls ( =0.03). The reduction in reoperation risk with ACD was not significantly influenced by patient age ( =0.51), sex ( =0.34), body mass index ( =0.21), smoking status ( =0.85), level of herniation ( =0.26), leg pain severity at baseline ( =0.90), or ODI at baseline ( =0.54). All patient-reported outcomes improved in each group from baseline to 4 years (all <0.001). The percentage of patients who achieved the minimal clinically important difference without a reoperation was proportionally higher in the ACD group compared to Controls for leg pain ( =0.07), ODI ( =0.10), PCS ( =0.02), and MCS ( =0.06). The addition of a bone-anchored ACD following lumbar discectomy in patients with large post-surgical annular defects reduces the risk of reoperation and provides better long-term pain and disability relief over 4 years compared to lumbar discectomy only.